Polyaniline (PANI)-conjugated tungsten disulphide (WS2) nanoparticles as potential therapeutics against brain-eating amoebae - Sumayah, Abdelnasir *; Mohammad Ridwane, Mungroo *; Shahabuddin, Syed; Siddiqui, Ruqaiyyah; Khan, Naveed Ahmed; Ahmad, Irfan; Ayaz, Anwar * (Springer Verlag (Germany), 2022)
Brain-eating amoebae, including Acanthamoeba castellanii and Naegleria fowleri, are the causative agents of devastating central nervous system infections with extreme mortality rates. There is an indisputable urgency for the development of effective chemotherapeutic agents for the control of these diseases that are increasing in incidence. Here, we evaluated the anti-amoebic potential of polyaniline:tungsten disulphide (PANI:WS2) nanocomposite against the infective trophozoite and cyst stages of N. fowleri and A. castellanii. Throughout these evaluations, significant viability inhibition was noted when 100 µg/mL of PANI:WS2 was employed at its 1:5 formulation. These effects were studied to be due to increased levels of reactive oxygen species (ROS) as visualised through fluorescence microscopy. Furthermore, field emission scanning electron microscopy (FE-SEM) analysis pictured disruption to amoeba morphology. The host-cell cytotoxicity of the nanocomposite (PANI:WS2) was studied to be negligible, making it an attractive avenue in the pursuit for effective treatments for brain-eating amoeba infections. KEY POINTS: • Synthesis of polyaniline:tungsten disulphide (PANI:WS2) nanocomposite. • Anti-amoebic potential of PANI:WS2 nanocomposite. • PANI:WS2 nanocomposites are promising anti-amoebic agents in vitro.